The impact of the MOOC based on the flipped classroom methodology to increase the level of information and information literacy competence in primary school teachers - Fernández-Otoya, Fiorela; Bravo, Jessie; Pérez-Postigo, Gerber; Alcázar-Holguin, Manuel Alfredo; Loaiza Chumacero, Sandra Cecilia (Frontiers in Education, 2025)
We live in an increasingly digitalized and competitive world, so the use of technological resources in continuing education is essential. The objective was to determine the impact of the MOOC based on the flipped classroom methodology on the level of information competence and information literacy in primary school teachers. The approach was quantitative, pre-experimental design. The sample consisted of 810 teachers from the Lambayeque region. After the MOOC application, it was found that the competency of navigation, search and filtering of information, data and digital content obtained the highest score, with 2.84 in the pretest and 3.67 in the posttest on a scale of 1 to 5. The conclusion is the need to train teachers so that they are able to respond effectively and efficiently to the new challenges of this digital society.